Les mères célèbres sur Instagram : ce que nous révèlent leurs mises en scène de l’allaitement - Chantal Bayard (Enfances, Familles, Générations, 2018)
Research Framework: In recent years, images of breastfeeding mothers have multiplied on social media. Censored until 2015, these images are now allowed on platforms like Facebook and Instagram. Unlike non-famous mothers, celebrities have followed the trend by publishing breastfeeding photographs on Instagram. The popularity of these women has helped to increase the visibility of breastfeeding in public spaces, a practice still criticized and perceived as being private. Objective: In this article, we seek to better understand the phenomenon of celebrities who publish photographs of breastfeeding on the social network Instagram. Methodology: We conducted a qualitative analysis of 50 breastfeeding photographs published, between January 2014 and August 2016, on the public and verified Instagram accounts of 13 celebrities practicing the professions of model, actress, singer and TV host. Results: Our research has shown that celebrity breastfeeding photographs on Instagram serve multiple purposes. They allow these women to mark their maternity in their family and professional trajectories while being advertising and participating in the development of their brand. They also participate in the construction of the social discourse in favor of the normalization of breastfeeding in the public space. Finally, the images published by celebrities on Instagram present a form of idealized maternity. Conclusions: Celebrity breastfeeding photographs depict "high-performance" mothers who breastfeed their child without difficulty, who readily combine work and breastfeeding, maintaining a neat physical appearance and postnatal body "in control". Through their images, these women offer an idealized way of being a mother, not accessible to the majority of women who consume their images on Instagram. Contributions: Our research captures the contribution of celebrities to the development of breastfeeding and maternity standards.